2019
DOI: 10.1021/acs.iecr.8b06107
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Catalytic Performance of Micro-Mesoporous Pt/Beta-KIT-6 Catalyst in n-Heptane Hydroisomerization Using Indexed Isomerization Factor and Experimental Verification

Abstract: A Beta-KIT-6 (BK) micro-mesoporous composite material was assembled using zeolite Beta seed solution as raw material. BK composite contained both zeolite Beta units and three-dimensional cubic Ia3d mesostructure of KIT-6, which served as a catalyst support for hydroisomerization of n-heptane. The composite was characterized by a variety of techniques. Results show that catalyst Pt/HBK using the composite as the support exhibited the highest isoheptanes yield among all catalysts, which is attributed to both app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…These images establish that the pore arrangement of the 0.8Pt@KIT−6 /SAPO−11 − 0.4 was more regular and that this material had an orderly strip−shaped pore structure. Standard KIT−6 molecular sieves contain ordered strip−shaped channels along the direction perpendicular to the channels and cubic three−dimensional pore structures can be observed along the direction of the pores 29 . In this work, the appearance of orderly strip−shaped pore structures in the prepared catalyst indicated that part of the undamaged structure of KIT−6 molecular sieve micron−sized fragments existed in the catalyst.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…These images establish that the pore arrangement of the 0.8Pt@KIT−6 /SAPO−11 − 0.4 was more regular and that this material had an orderly strip−shaped pore structure. Standard KIT−6 molecular sieves contain ordered strip−shaped channels along the direction perpendicular to the channels and cubic three−dimensional pore structures can be observed along the direction of the pores 29 . In this work, the appearance of orderly strip−shaped pore structures in the prepared catalyst indicated that part of the undamaged structure of KIT−6 molecular sieve micron−sized fragments existed in the catalyst.…”
Section: Resultsmentioning
confidence: 53%
“…Standard KIT−6 molecular sieves contain ordered strip−shaped channels along the direction perpendicular to the channels and cubic three−dimensional pore structures can be observed along the direction of the pores. 29 In this work, the appearance of orderly strip−shaped pore structures in the prepared catalyst indicated that part of the undamaged structure of KIT−6 molecular sieve micron−sized fragments existed in the catalyst. The particle size distribution data demonstrate that the Pt nanoparticles on all three catalysts were well dispersed and that the average Pt particle size was in the range of 5.2-5.7 nm.…”
Section: Catalytic Reactionsmentioning
confidence: 56%
See 1 more Smart Citation
“…The MoBC 7 fraction includes 2methylhexane (2-MeC 6 ), 3-methylhexane (3-MeC 6 ), and 3-ethylpentane (3-EtC 5 ). 3-MeC 6 is slightly favoured against 2-MeC 6 (see 2-MeC 6 /3-MeC 6 ratio), especially with the composite catalysts, which can be recognized as the weaker diffusion restriction [72,73]. The results (Table 3) have revealed that among the Pt composite catalysts, the Pt/SBA-BEA shows the highest efficiency in iso-C 7 products with relatively high contribution of MuBC 7 .…”
Section: Effect Of the Type Of Zeolite Incorporated To Pt/alsba-15-zeolitementioning
confidence: 91%
“…This method is widely used because of its low cost and simple operation process [19] . Some researchers have processed mordenite, [16a] ZSM‐5, [20] Beta [21] and other zeolites to prepare micro‐meso materials and tested their catalyst performances. Compared with the samples without treatment, the treated ones performed better.…”
Section: Introductionmentioning
confidence: 99%